1995
DOI: 10.3354/dao021187
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic characterization of Enterococcus strains pathogenic for turbot and their relationship with other Gram-positive bacteria

Abstract: We describe here the serological and antigenic characterization of a group of highly virulent Enterococcus strains that, since 1993, have caused heavy economic losses in turbot Scophthalmus maximus reared in northern and northwestern Spain. Reference Gram-positive strains and the corresponding polyclonal antisera raised against some species of lactic acid bacteria as well as Corynebacterium aquaticurn and Renibacterium salmoninarum were included. Agglutination assays demonstrated that regardless of the farm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…For this study, the isolate RA-99.1 of Streptococcus parauberis, recovered in 1993 from diseased turbot in our laboratory, was chosen as the representative strain since, as previously described (Toranzo et al , 1995, all the fish isolates show a high phenotypic and genetic homogeneity. Reference strain S. parauberis NCDO 2020, isolated from cattle in 1995, was included in all the experiments for comparative purposes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this study, the isolate RA-99.1 of Streptococcus parauberis, recovered in 1993 from diseased turbot in our laboratory, was chosen as the representative strain since, as previously described (Toranzo et al , 1995, all the fish isolates show a high phenotypic and genetic homogeneity. Reference strain S. parauberis NCDO 2020, isolated from cattle in 1995, was included in all the experiments for comparative purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Reference strain S. parauberis NCDO 2020, isolated from cattle in 1995, was included in all the experiments for comparative purposes. The phenotypic and serological characteristics of the isolates have been described elsewhere (Toranzo et al , 1995.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doménech et al (1996) was the first to identify S. parauberis as a fish pathogen for the isolates from diseased turbot Scophthalmus maximus by analyzing the 16S rRNA gene. Another group reported that this pathogen caused high economic losses in turbot culture in Spain (Toranzo et al, 1995). Since then, streptococcicosis caused by S. parauberis had been limited to turbot and Japanese flounder Paralichthys olivaceus cultured in Spain and Korea, respectively (Toranzo et al, 2005;Baeck et al, 2006).…”
mentioning
confidence: 99%
“…Epidemic and sporadic diseases have been reported from different parts of the world, notably Japan (Kitao 1993), Singapore (Foo et al 1985). Australia (Carson et al 1993), Israel (Eldar et al 1995), Italy (Ghittino & Prearo 1992), Spain (Toranzo et al 1995, Domenech et al 1996, France (Michel et al 1997), South Africa (Braag & Broere 1986) and the United States (Perera et al 1994). Amended taxonomy reveals that at least 6 different species of Gram-positive cocci, including streptococci (Pier & Madin 1976, Domenech et al 1996, lactococci (Collins et al 1984, Williams et al 1990, Domenech et al 1993, Eldar et al 1996, and vagococci (Wallbanks et al 1990), are responsible for such conditions.…”
mentioning
confidence: 99%